The 15th International ISAAC Congress - Suragan, Durvudkhan; Sabitbek, Bolys (Bulletin of the Karaganda University. Mathematics Series, 2024)
Nazarbayev University in Astana, Kazakhstan, will host the 15th International ISAAC Congress from July 21–25, 2025. The International Society for Analysis, its Applications, and Computation (ISAAC) Congress is a prestigious event that continues a successful series of meetings previously held across the globe.